Intergenerational changes in birth parameters in Kraków (Poland) in the context of socio-economic transformation from 1985–2010. (21st August 2013) - Kryst, Łukasz
Abstract: Background : Analyses of birth parameters worldwide reveal relatively high variability over time, often related to socioeconomic factors. Aim : The aim was to determine the existence of inter-generational changes in birth parameters in Kraków (Poland) in recent years and factors responsible. Subjects and methods : This research analysed data on 7800 newborns (e.g. body length and weight) and their parents in the years 1985–2010. The significance of differences was calculated using ANOVA. To examine the potential effect of environmental factors, MANOVA were used. Results : In the case of birth weight no significant changes were observed. A significant decreasing tendency in birth length from the beginning of the 21st century was shown – this observation is quite rare. Accordingly, BMI increased significantly in the 2000s. A decreasing tendency was observed for head circumference. Conclusion : In the analysed period Poland experienced significant socio-economic changes, which could have partly contributed to the observed changes. Some of the observed trends in birth parameters are recent phenomena and it seems necessary to continue the research to confirm if these changes form a steady trend or are only temporary. Tracking any phenomena related to the development is important for the determination of disruptive factors and the reduction of their adverse effects.